Generał broni Władysław Anders 1892-1970 : czyny i pamięć - Kirszak, Jerzy; Polak, Bogusław; Polak, Michał (2022)
Lieutenant-General Wladyslaw Anders (1892-1970) was a General in the Polish Army, then a politician with the Polish government-in-exile in London. After the war his soldiers were repressed, and the memory about the General tried to erase from the consciousness of Polish society